Dominasi Kuasa pada Pemilihan Kepala Desa Serentak di Kabupaten Halmahera Selatan Provinsi Maluku Utara - Marno Wance; Raoda M. Djae (Universitas Muhammadiyah Ponorogo, 2019)
Political power occurring in the village heads elections is a part of political power contestation wave started simultaneously in 2015. South Halmahera Regency is one of the regions participating in this political power contestation. At the contestation process, it is seen that the village residents are divided into some divisions based on their political choices. This situation continues to happen in the simultaneous village head elections in South Halmahera Regency in 2016. It attracts political actors to be involved in intervening power and dominance to win the contestation. Therefore, political power is used to carry out the basis of consolidation for winning the elections. This political power treats long-term power because the greater base of political power at the village level has been formed. The expected benefit of this study is to expand our horizon on political power issues, particularly in the village head elections context. Practically, this study can contribute to study material from various interested parties to analyze electoral conflicts that occur at the lowest level such as at Babang Village and Marabose Village. Besides that, the study also sees the involvement of regional actors and local governments in intervening to dominate power using the authority they have.